1
$\begingroup$

I'm stuck on this one. I've tried integration by parts but to no avail:

$$\int_{0}^{4} x e^{ (x-2)^4 } dx = \left[ x \int e^{ (x-2)^4 } dx \right]_{0}^{4} - \underbrace{\int_{0}^{4} e^{ (x-2)^4 } dx}_{=k} $$

I suspect this is a dead end. I think there's some simple trick here I'm missing. Any hints are appreciated.

$\endgroup$
2
$\begingroup$

$$ I = \int_{0}^{4} xe^{(x-2)^4} \quad dx $$ substitute $t = 4-x$

$$ \begin{align} I &= \int_{4}^{0} (4-t)e^{(4-t-2)^4} \quad (-dt) &= \int_{0}^{4} (4-t)e^{(t-2)^4} \quad dt \end{align}$$ Adding the 2 results $$\begin{align} 2I = 4 \int_{0}^{4} e^{(x-2)^4} \quad dx & = 4k \end{align} $$

$\endgroup$
0
$\begingroup$

Note that

$$k = \int_{-2}^2 dx \, e^{x^4} $$

Then

$$\int_0^4 dx \, x \, e^{(x-2)^4} = \int_{-2}^2 dx \, (x+2) e^{x^4} = 2 \int_{-2}^2 dx \, e^{x^4}= 2 k$$

Note that the result desired comes out of symmetry, as clearly

$$\int_{-2}^2 dx \, x \, e^{x^4} = 0$$

$\endgroup$
0
$\begingroup$

Well, the function $(x-2)\,e^{-(x-2)^4}$ is continuous and symmetric with respect to $x=2$, hence its integral over $(0,4)$ is zero. The claim easily follows through $x=(x-2)+2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.